Effect of Modification Rules in Competition on Technical–Tactical Action in Young Tennis Players (Under-10) - Gimenez-Egido, José María; Ortega-Toro, Enrique; Palao, José M.; Verdú-Conesa, Isidro; Torres-Luque, Gema (Frontiers in Psychology, 2020)
Adapting competitions to young players’ characteristics is an important pillar in the optimal teaching–learning process. The objective of the present study is to analyze the effect of modifying net height (from 0.91 to 0.80 m) and court dimensions (from 23.77 × 8.23 m to 18 × 8.23 m) for under-10 (U-10) tennis players on the following: (a) kinds of technical and tactical basic, situational, and special strokes; (b) tennis players’ hitting area; (c) landing location of the serve; (d) ball landing location after the serve; (d) stroke effectiveness; and (e) rally length. The study design was quasi-experimental in nature, observing the fluctuation/change in technical–tactical variables of the tennis players when playing a “Tennis 10s Green Competition” (GC) with the current federative rules and a redesigned competition “Modified Competition” (MC) including altered net height and court dimensions based on small-sided games (SSGs) and equipment scaling. Twenty U-10 tennis players were studied (age of players = 9.46 ± 0.66 years, average weekly training in tennis = 2.90 ± 1.07 h, years of experience = 3.65 ± 1.53 years). The results showed that in MC, there was a greater technical–tactical variability compared with the GC in terms of the following: (a) greater service effectiveness; (b) more situational and special strokes; and (c) a more equitable change in the distribution of hitting and ball landing locations. The values of MC showed that the current adaptation rules and equipment in federated U-10 competitions might not be enough to improve the teaching–learning process under the comprehensive approach. The current competition for U-10 tennis players (stage green) should be redesigned, in order to build an optimal process of affordances to develop a multidimensional positive impact during this training stage.